Is a Guaranteed Living Wage a Good Anti-Poverty Policy? - Murgai, Rinku; Ravallion, Martin (World Bank, Washington, DC, 2012)
Minimum wages are generally thought to be unenforceable in developing rural economies. But there is one solution - a workfare scheme in which the government acts as the employer of last resort. Is this a cost-effective policy against poverty? Using a microeconometric model of the casual labor market in rural India, the authors find that a guaranteed wage rate sufficient for a typical poor family to reach the poverty line would bring the annual poverty rate down from 34 percent to 25 percent at a fiscal cost representing 3-4 percent of GDP when run for the whole year. Confining the scheme to the lean season (three months) would bring the annual poverty rate down to 31 percent at a cost of 1.3 percent of GDP. While the gains from a guaranteed wage rate would be better targeted than a uniform (untargeted) cash transfer, the extra costs of the wage policy imply that it would have less impact on poverty.